Status Nutrisi Siswa TK Labschool Lidah Wetan dan Ketintang Surabaya - Abidah, Hafshah Yasmina; Anjani, Nur Ilahi; Sasongko, Devi Purnamasari (Poltekkes Kemenkes Bengkulu, 2025)
There is insufficient information on the nutritional status of kindergarteners, especially in Surabaya. This study's primary goal is to present information on the nutritional status of kindergarten children enrolled at Labschool Lidah Wetan and Ketintang, Surabaya. Cross-sectional descriptive study of students aged 4-7 years (n = 56), with anthropometric measurements for weight and height of the students using a digital weight and height scale. After obtaining the students' weight and height data, Z-score measurements were conducted according to the WHO curve for height-for-age (H/A), weight-for-age (W/A), and body mass index-for-age (BMI/A). The findings showed that three students (5.4%) were classified as short, fifty-two students (92.9%) as normal, and one student (1.8%) as tall for H/A measurement. According to the W/A measurement results, one student (1.8%) was classified as severely thinness, two (3.6%) as thinness, forty-eight (85.7%) as normal, and five (8.5%) as overweight. Nine students (16.1%) were classified as thin, forty students (71.4%) as normal, three students (5.4%) as overweight, and four students (7.1%) as obese based on the BMI/age measurement. Overall, kindergarten students at Labschool Lidah Wetan and Ketintang Surabaya had generally good nutritional status.